Enhancing Security in On-Chip Communication: A Survey of Threats and Solutions - Win, Thinzar Aung (Journal of ISMAC, 2024)
As the complexity of integrated circuits (ICs) continues to increase, ensuring the security of on-chip communication becomes paramount. With the rise of interconnected devices and the Internet of Things (IoT), vulnerabilities in on-chip communication pose significant risks to data integrity, privacy, and system reliability. This article presents a comprehensive survey of the threats and solutions associated with enhancing security in on-chip communication. The survey begins with an overview of on-chip communication and its critical role in modern ICs. It then explores the diverse range of security threats faced by on-chip communication systems, including side-channel attacks, information leakage, unauthorized access, and the insertion of hardware Trojans. Each threat is examined in detail, highlighting its characteristics and potential impact on system security. In response to these threats, the survey examines various solutions and countermeasures aimed at enhancing on-chip communication security. These include encryption and authentication techniques, secure routing protocols, hardware-based security mechanisms, and software-based security solutions. Examples of real-world security breaches and successful implementations of security solutions are also presented to provide practical insights.
Keywords: Security Threats; Security Solutions; Side-Channel Attacks; Information Leakage; Unauthorized Access; Hardware Trojans